How Ambidextrous Marketing Capabilities Mediate the Impact of Market Knowledge Breadth on Innovation Performance: A Conceptual Model - Muhammad Dharma Tuah Putra Nasution; Yossie Rossanty; Ramadhan Harahap; Aulia Ramadhan Tanjung (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This conceptual paper aims to explore the mediating role of ambidextrous marketing capabilities in the relationship between market knowledge breadth and innovation performance within the hospitality sector, specifically in food and beverage establishments. This study addresses a critical gap in the literature by proposing a theoretical framework that links these variables. It conceptualizes how a firm’s breadth of market knowledge—encompassing insights into various market segments and customer needs—can influence its innovation performance, with ambidextrous marketing capabilities acting as a mediating factor. Ambidextrous marketing capabilities are defined in terms of their exploratory (ability to explore new markets and customer segments) and exploitative (ability to leverage existing market knowledge) dimensions. The paper argues that firms with extensive market knowledge are better positioned to develop and apply these capabilities effectively, thus enhancing their innovation outcomes. The proposed framework suggests that market knowledge breadth influences innovation performance both directly and indirectly through ambidextrous marketing capabilities. This conceptual approach aims to provide a foundation for future empirical research and offers theoretical insights into how firms in the hospitality sector can leverage their market knowledge and marketing capabilities to drive innovation.